Reward and Punishment to Students’ Learning Motivation in Hybrid Learning: Digging Teachers’ Perspectives - Febrianto, Aldian Idris; Priyana, Joko (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research focuses on teachers’ strategy, rewards and punishments teaching strategy in enhancing EFL students’ learning motivation. In addition, this research also aims to provide teachers’ perspectives about the use of rewards and punishments strategy to improve students’ motivation and efficiency as EFL learners during hybrid learning. Methodology: Descriptive qualitative design with interviews in the class were used to gather the teachers’ perspectives and to see the on-site implementation of rewards-punishments strategy toward students’ learning motivation. Besides, the researchers also highlight the technology used by the teachers in their hybrid learning process. Main Findings: The results indicate that a balanced strategy by combining suitable motivational techniques with emerging technology can significantly enhance teachers' effectiveness and morale in a hybrid learning environment which can increase students’ learning motivation. In other words, rewards become learning motivation booster for students and teachers’ supports in the form of positive feedback are also found to be beneficial to boost students’ confidence in learning English. Novelty/Originality of this study: This research contributes to the ongoing conversation about improving students’ learning motivation and teachers’ teaching strategy in hybrid learning. Covering the knowledge gap of reward and punishment implementation in hybrid class, specifically for junior high school students.